When to grit and when to quit: (How) should grit be taught in K-12 classrooms?. Issue 3 (3rd July 2022) - Audley, Shannon; Donaldson, Maleka
ABSTRACT: Educational lore casts grit as a panacea for solving long-standing achievement disparities. Fifteen years of empirical research has not supported this claim, yet many schools still uphold grit. Why? This article examines when (and if) K-12 educators should emphasize grit in classrooms. We first define the construct and offer evidence-based critiques of grit's conceptual claims. Next, we discuss grit's influence on school achievement, which has, at best, a negligible impact on school achievement. However, at worst, grit reifies social inequalities by boosting the performance of already-privileged individuals and harming minoritized groups and those in under-resourced learning contexts. Finally, we argue that grit does not compensate for adverse circumstances—including poverty, racial/ethnic discrimination, dis/abilities, and intersections—but instead reinforces privilege. Building on these insights, we close with several recommendations for policymakers, schools, and teachers to reduce the inequitable opportunity gaps that undermine achievement and support students with research-based interventions.